Empowering African Youth Pastoralists: Insights on COP28 from East Africa lead of the African Youth Pastoralist Initiative (AYPI) COP28 - Masanja, Josephat (ILRI, 2023)
Reflections from Josephat Masanja on his participation in UNFCCC COP28, Dubai 2023, and implications for the growth of the African Youth Pastoralist Initiative.